Investigation of the Supply Chain Management and Cash Balances Impact on Planning - Hamad Obaid, Mohanad; Rashid Salih, Murtada; Frayyeh Hassan, Mohammed (International Journal of Supply Chain Management, 2019)
Cash reserves of bank, including bill, coins and check, which are used for daily operation of customers, shall be managed so that in spite of covering the risk of liquidity, arising from cash deficit, the cost of cash excess stagnation is minimized. Therefore, the aim of this study is to optimize the remained cash of banks branches fund. To determine the optimum limit of money in the funds, we used two approaches of time series and propagation model 4 and prediction was conducted monthly and seasonally. The function of possible distribution of deposits and withdrawals of branch customers' cash and required net liquidity as well as the function of time distribution of cash deposit and withdrawal were used in the propagation model. The used data were daily gathered in the time intervals of 2016-2017 from the selected branches. Using the conducted stimulation, in addition to determine the optimal limit of money maintenance in fund, money limit was 25% reduced in comparison with current situation.